Exploring consumersâ perception and willingness to pay for âNon-Added Sulphiteâ wines through experimental auctions: A case study in Italy and Spain - Mario Amato; Petjon Ballco; Belinda LÃ³pez-GalÃ¡n; Tiziana De Magistris; Fabio Verneau (Wine Economics and Policy)
Although scientific literature is still uncertain towards the real causes that can link headache episodes with moderate wine consumption, a growing proportion of consumers seems to address sulphites as possible culprits. Hence, the objective of this study is to assess consumers` willingness to pay for wine bearing a sulphites-free label in two traditional wine producing countries, Italy and Spain. The methodological framework is based on the specification of the Becker-DeGroot-Marschak (BDM) type of auction applied to consumers purchasing wine in the supermarket stores of both countries. A left censored Tobit model is used to analyse the bidding behaviour for conventional and 'Non-Added Sulphite' (NAS) wine. Results in both countries show that consumers who link the headaches with the consumption of sulphite are willing to exchange the habitually consumed bottle of wine with a NAS wine and pay extra premium prices. Keywords: Experimental auctions, Non-added sulphite wines, Consumer behavior